Peningkatan Pengetahuan Masyarakat dengan Pendampingan Formulasi Handsanitizer Standar WHO di Kelurahan Mojosongo, Surakarta - Dian Eka Ermawati; Anif Nur Artanti; Sholichah Rohmani; Wisnu Kundarto (Universitas Mathla'ul Anwar Banten, 2022)
INCREASING PUBLIC KNOWLEDGE WITH ASSISTANCE IN WHO STANDARD HANDSANITIZER FORMULATION IN MOJOSONGO VILLAGE, SURAKARTA. The Applied Pharmacy Research Group has a service roadmap that examines medicinal products, supplements, cosmetic and traditional medicines that can contribute and be adopted by society. One of the issues is liquid dosage form formulation. Alcohol is the one of choice after washing hands with soap. The use of hand sanitizer can deactivate microorganisms that stick to hand. This increase in use because pandemic covid-19 that made many people take preventive action. One way to prevent the spread of the Corona virus is maintain cleanliness such as diligently washing hands with soap and water. In the other hand the use of handsanitizer is also recommended when you cannot reach water and soap. Activity community service in Mojosongo Village, focuses on increasing public knowledge in formulate liquid Handsanitizer that is practical and simple according to the standards requirment by WHO (World Health Organization). The results of the questionnaire conducted before and after assistance in making hand sanitizers stated that most of the respondents had showed an increase in knowledge related to components in the manufacture of handsanitizers